Gratuidade da justiça no direito previdenciário: busca pelo direito fundamental à prova e a necessidade de definição de critérios para sua concessão - Schmitz, Luna (Universidade do Vale do Rio dos Sinos, 2025)
This dissertation analyzes the effectiveness of free legal aid in social security law, highlighting its relationship with the fundamental right to evidence and the need to establish objective criteria for its granting. The study is based on the premise that, although free legal assistance is a constitutionally guaranteed right, its implementation in the social security sphere faces obstacles that limit access to justice, especially for economically vulnerable claimants. The research question posed is: does the absence of objective criteria for granting free legal aid compromise the guarantee of the fundamental right to evidence and, consequently, access to justice itself? The hypothesis suggests that the lack of clear parameters for the granting of this benefit results in arbitrary judicial decisions, generating legal uncertainty and inequality among litigants. The general objective of the research is to analyze the challenges and limitations of free legal aid in social security law, aiming to demonstrate how the absence of defined criteria can hinder the effectiveness of the fundamental right to evidence. The dissertation is organized into two chapters. The first analyzes the effectiveness of free legal aid in the context of social security, based on its origins, comparative legal application, national regulation, and current limitations. The second chapter addresses the fundamental right to evidence as an expression of access to justice, investigating the impacts of procedural costs, the regional and social inequalities faced by claimants, and the need for legislative regulation of free legal aid. The research adopts the deductive method, with a qualitative approach, bibliographic review, and analysis of concrete cases. It concludes that the limitation on the funding of medical expert examinations in social security proceedings—without provision for other necessary technical examinations—undermines the effectiveness of free legal aid and reinforces inequalities in access to justice. Therefore, a legislative review is necessary to broaden the coverage of procedural costs, ensuring the full realization of the fundamental right to evidence and promoting social justice within the scope of social security.
Keywords: Gratuidade da justiça; Direito fundamental à prova; Acesso à justiça; Segurados hipossuficientes; Direito Previdenciário; Perícias judiciais; Free legal aid; Fundamental right to evidence; Access to justice; Economically vulnerable claimants; Social security law; Judicial expert examinations; ACCNPQ::Ciências Sociais Aplicadas::Direito